A review on recent advances in photodegradation of dyes using doped and heterojunction based semiconductor metal sulfide nanostructures for environmental protection. (September 2018) - Ayodhya, Dasari; Veerabhadram, Guttena
Abstract: Among the admired photocatalysts, metal sulphide-based semiconductors are most prominent photocatalysts for the degradation or decomposition of dyes in wastewater industries with low cost, environment-friendly and sustainable treatment technologies for the environmental protection. In recent years, the environmental pollution poses a serious threat to the environment and public health. To overcome the environmental pollution, doped and heterojunction based semiconductor metal sulfide nanostructures (MSNSs) are developed as photocatalysts for the purpose of photocatalytic degradation or removal of large organic dyes in an eco-friendly and sustainable fashion. This comprehensive review starts with a brief overview on dyes as pollutants, dyes classification, dyes decolorization or degradation strategies and focuses on the mechanisms involved in comparatively well understood MSNSs photocatalysts such as ZnS, CdS, CuS, Ag2 S, Bi2 S3, CoS, FeS, and PbS etc. It particularly discusses the recent advancements to enhance photocatalytic degradation of toxic dyes by using various MSNSs to make it a flexible and cost-effective commercial dye treatment technology. In addition, we have focused on the treatment of organic dyes using different types of MSNSs by photocatalysis and the effects of various parameters such as dopants, heterojunctions, band gap, size, light intensity, surface area, reaction time, and degradation efficiency, etc., are highlighted. Graphical abstract: Highlights: A state of art review on heterogeneous photocatalysis for degradation of dyes. This review summarizes the recent trends of semiconductor MSNSs in photocatalysis. Doped semiconductor MSNSs are superior photocatalysts for dyes degradation. Heterojunction semiconductor MSNSs are famous photocatalysts for dyes degradation. The degradation of dyes is effected by size, surface area and amount of catalyst.